1983
DOI: 10.1111/j.1476-5381.1983.tb10006.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses of rats to intrahypothalamic injection of carbachol and noradrenaline

Abstract: Carbachol (0.1–2 μg) and noradrenaline (5–20 μg) injected into the anterior hypothalamus of unanaesthetized unrestrained rats evoked dose‐dependent falls in heart rate and increases in arterial blood pressure. When the above amine injections were repeated in rats anaesthetized with chloral hydrate, sodium pentobarbitone or halothane the evoked bradycardias were usually smaller and the changes in arterial blood pressure more variable. The cardiovascular responses to carbachol (1 μg) and to noradrenaline (10 μg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…application of carbachol not only produced pressor responses in the nearterm ovine fetus but also increased the neural activity in the putative central cardiovascular controlling centers. The finding that c-fos expression was induced in the fetal AV3V and the hindbrain is the evidence that the central pathway are activated and cholinergic mechanisms are functional in the control of fetal blood pressure at 90% gestation, and indicates that the fetal AV3V region in the forebrain and In mature animals, carbachol is known as a long-lasting cholinergic agonist in the brain in affecting body fluid and cardiovascular homeostasis, including increase of arterial blood pressure, release of vasopressin, and stimulation of thirst (Barbosa et al, 1995;Iitake et al, 1986;Mahon et al, 1995;Poole, 1983). Previous studies in adults showed that the pressor response induced by central administered carbachol was marked and sustained with short latency (Poole, 1983;Ö zkutlu et al, 1994).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…application of carbachol not only produced pressor responses in the nearterm ovine fetus but also increased the neural activity in the putative central cardiovascular controlling centers. The finding that c-fos expression was induced in the fetal AV3V and the hindbrain is the evidence that the central pathway are activated and cholinergic mechanisms are functional in the control of fetal blood pressure at 90% gestation, and indicates that the fetal AV3V region in the forebrain and In mature animals, carbachol is known as a long-lasting cholinergic agonist in the brain in affecting body fluid and cardiovascular homeostasis, including increase of arterial blood pressure, release of vasopressin, and stimulation of thirst (Barbosa et al, 1995;Iitake et al, 1986;Mahon et al, 1995;Poole, 1983). Previous studies in adults showed that the pressor response induced by central administered carbachol was marked and sustained with short latency (Poole, 1983;Ö zkutlu et al, 1994).…”
Section: Discussionmentioning
confidence: 94%
“…Central application of carbachol, a nonselective cholinergic agonist, produces an increase of blood pressure (BP), vasopressin release, and drinking (Barbosa et al, 1995;Iitake et al, 1986;Mahon et al, 1995;Poole, 1983). However, investigation of the development of brain cholinergic systems and their roles in cardiovascular homeostasis in utero has been very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Direct injection of norepinephrine, epinephrine and clonidine into the AHA results in dose-related decreases in blood pressure and heart rate in rats [33][34][35]. Furthermore, in spontaneously hypertensive rats, hypertension induced by a high NaCl diet is associated with a reduced norepinephrine release in the AHA [17,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, Poole reported that the microinjection of NA into POA in rats increases arterial pressure. 24 The POA receives major noradrenergic innervation from the locus coeruleus (LC) and the other cell groups in the medula oblongata and pons. Noradrenergic neurons in the LC are strongly activated during recovery from halothane anesthesia.…”
Section: Discussionmentioning
confidence: 99%